Case Report: One-Year Delay in the Effect of Conversion Surgery Therapy for Advanced Hepatocellular Carcinoma After Systemic Therapy - Xie, Qing-Yu; Liu, Hai-Yan; Guo, Ze-Yi; Wu, Yan-Ping; He, Guo-Lin; Cai, Lei; Pan, Ming-Xin; Fu, Shun-Jun (Frontiers in Molecular Biosciences, 2022)
Hepatocellular carcinoma (HCC) is the sixth most commonly diagnosed malignancy and the third leading cause of cancer-related deaths worldwide. A 58-year-old man with HCC visited local hospital due to abdominal discomfort and was diagnosed with unresectable HCC with lung metastasis. After admitting to our hospital in April 2020, he received two cycles transcatheter arterial embolization (TAE), hepatic arterial infusion chemotherapy (HAIC-Folfox), sorafenib and camrelizumab every 3 weeks. Due to the end of HAIC treatment, he performed once drug-eluting transcatheter arterial chemoembolization (dTACE), sorafenib and camrelizumab. However, because worsening liver function, we interrupted TACE and only gave sorafenib and camrelizumab in August 2020. Although he received systemic therapy, the tumors still rapidly progressed and we considered the possibility of tumor resistance. Subsequently, regorafenib was given. In September, the patient performed once conventional TACE (cTACE), regorafenib and camrelizumab. After half a year of comprehensive treatment, the treatment effect was not satisfactory, and he returned to the local hospital to received regorafenib everyday and camrelizumab once every 3 weeks. The patient found that the tumor and lung metastasis had shrunk significantly after one year of the initial diagnosis, then he was admitted to our hospital and received surgery treatment, and now he has survived disease-free for 6 months.